Aspek Kepribadian Tokoh Pada Novel Si Anak Kuat Karya Tere Liye Dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia DI SMA - Alan Budiawan Alan Budiawan; Sutji Muljani; Syamsul Anwar (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
The purpose of this research is to describe the personality aspects of the characters in Tere Liye's The Strong Child novel. Describe the implications of research results in learning Indonesian in high school. This research use desciptive qualitative approach. The source of the data in this study is in the form of sentences in the novel Si Anak Strong by Tere Liye. The form of data used in this research is the structure of the character's personality and the dynamics of the character's personality. The data collection technique used in this study is a reading and note taking technique. The data analysis technique used is descriptive qualitative. The results of this study can be found in the form of personality structure and personality dynamics. (1) In the form of personality structure there are 22 data. (2) In the form of personality dynamics there are 25 data. The implications of the research results for Indonesian language learning are applied to basic competencies X KD 3.8 interpreting the author's view of the novel's life. Class Xll high school level semester 2.